REMPAH NUSANTARA DALAM SENI LUKIS PADA MEDIA TALENAN DENGAN TEKNIK 3D - Suyasa, I Nyoman; Rahman, Deni -; Mahendrapati, Alexander Nawangseto (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2022)
The research entitled “Rempah Nusantara dalam Seni Lukis pada Media Talenan dengan Teknik 3D” is applied research based on the development of painting which functions as a medium of information about the natural wealth of the archipelago. Aside from spices and medicineherbscesis  are also very suitable to be used as a source of ideas in the creation of works of art. Because spices have various and unique shapesattarstractive colors. Using applied research methods with various stags, including: observation of objects or observations, contemplation, experimentation, fo,rmation, work and presentation. This research is focused on creating innovative works of art with the theme of Indonesian spices on cutting boards techniques technique, so that the spices look as real as they are on a cutting board. The purpose of this research is to reintroduce native Indonesian spices to the wider community with the medium of painting, as well as to explore new possibilities in terms of developing techniques that are more innovative and have an economic impact.